2022
DOI: 10.1007/s11846-022-00569-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of dynamic capabilities on SME performance during COVID-19

Abstract: Dynamic capabilities (DCs) are a growing field of research within the scope of theoretical structures based on resource and strategic management. Given the demonstrated impact of DCs on company performance, it is important to study the effects of DCs on small and medium sized enterprises (SMEs) within the context of the COVID-19 pandemic. Hence, this research evaluates the role of DCs during the pandemic and its impact on the performance levels of SMEs. Analysing the responses of 209 SMEs using a structural eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
33
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 110 publications
10
33
0
3
Order By: Relevance
“…The present SDGs of the UN 2030 Agenda for Sustainable Development require rethinking sustainability because they are not resilient enough to pandemic shock ( Ibn-Mohammed et al, 2021 ). A measurement mechanism for COVID-19′s influence on progress towards sustainability pillars and sustainable development is also necessary ( Dejardin et al, 2022 ). Because COVID-19 is so new, the lack of an acceptable and effective measurement tool for sustainability monitoring and assessment necessitates future research.…”
Section: Reflections and Directions For Future Researchmentioning
confidence: 99%
“…The present SDGs of the UN 2030 Agenda for Sustainable Development require rethinking sustainability because they are not resilient enough to pandemic shock ( Ibn-Mohammed et al, 2021 ). A measurement mechanism for COVID-19′s influence on progress towards sustainability pillars and sustainable development is also necessary ( Dejardin et al, 2022 ). Because COVID-19 is so new, the lack of an acceptable and effective measurement tool for sustainability monitoring and assessment necessitates future research.…”
Section: Reflections and Directions For Future Researchmentioning
confidence: 99%
“…Considering that such pandemic crises have increased in frequency in the last century ( Kraus et al, 2020 ), our study is among the first to deliver evidence on developing preparation resilience to this important type of crisis and thus moves beyond existing qualitative evidence ( Fath et al, 2021 ) and conceptual pieces ( Beninger and Francis, 2022 ) on preparation resilience in light of the COVID-19 crisis. We thus extend empirical research that has focused on coping and adaption resilience in response to COVID-19 ( Bartik et al, 2020 ; Dejardin et al, 2022 ; Emami et al, 2021 ; Giotopoulos et al, 2022 ; Hadjielias et al, 2022 ; Hammerschmidt et al, 2021 ; Kraus et al, 2020 ; Khurana et al, 2022 ; Kusa et al, 2022 ; Schwaiger et al, 2022 ; Soluk et al, 2021 ; Wendt et al, 2021 ; Xie et al, 2022 ) by adding the notion that digitalization can be considered to be a preparation form of organizational resilience ( Duchek, 2020 ), but does not equip all types of organizations equally well to withstand the impact of pandemic crises. That is, different to some of these recently published papers (e.g., Giotopoulos et al, 2022 ; Schwaiger et al, 2022 ; Wendt et al, 2021 ), we did not find that organizational size, strategy, industry affiliation, or past performance materially affect the resilience emanating from the preparation capability of digitalization.…”
Section: Discussion Implications and Limitationsmentioning
confidence: 98%
“…With this focus on digitalization before the crisis as a preparation capability, we aim to complement earlier research that has examined entrepreneurial firms' responses to the pandemic crisis caused by COVID-19 (e.g., Bartik et al, 2020 ; Dejardin et al, 2022 ; Emami et al, 2021 ; Giotopoulos et al, 2022 ; Hadjielias et al, 2022 ; Hammerschmidt et al, 2021 ; Kraus et al, 2020 ; Khurana et al, 2022 ; Kusa et al, 2022 ; Schwaiger et al, 2022 ; Soluk, 2022 ; Soluk et al, 2021 ; Wendt et al, 2021 ; Xie et al, 2022 ), and thus into coping and adaption forms of organizational resilience ( Duchek, 2020 ). In general, these earlier findings highlighted the significant variance among entrepreneurial firms' responses to the COVID-19 pandemic crisis (e.g., Hadjielias et al, 2022 ; Sharma et al, 2022 ), including their reliance on digital technologies ( Giotopoulos et al, 2022 ; Khurana et al, 2022 ; Soluk, 2022 ; Soluk et al, 2021 ; Wendt et al, 2021 ).…”
Section: Literature Review Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…While we experience a slowing down of economic factors, additionally, it has been shown that the pandemic has negatively affected entrepreneurship (Galindo-Martín et al 2021). One might believe that a crisis mobilizes creativity and entrepreneurship (Peris-Ortiz et al 2014;Dejardin et al 2022). Still, these positive triggers have mostly been related to vaccination development, testing services, virtual work delivery services, and home and garden solutions.…”
Section: A Glimpse Of How Crises Affect Entrepreneurship and Innovationmentioning
confidence: 99%